PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP HASIL BELAJAR IPA DI TINJAU DARI KETERAMPILAN BERPIKIR KRITIS SISWA KELAS VIII SMP NEGERI 1 TEPUS GUNUNGKIDUL TAHUN AJARAN 2013/2014 - Susi Murtini; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
TheÂ  research aims to know the result of learning natural science of SMP Negeri 1 Tepus Gunungkidul school year 2013/2014 which through quantum teaching learning and direct instruction. In comparative term in the research to determine the differences in the result ofÂ  learning natural science eight grade student in SMP Negeri 1 Tepus Gunungkidul school year 2013/2014 at the between used quantum teaching learning and direct instruction in terms of critical thinking skill.This research did in SMP Negeri 1 Tepus Gunungkidul in academic 2013/2014. The population in the research was 126 students at the eight grade from four classes. This research in clude on descriptive comparatif. Was like â€œquasi eksperimentâ€. The sample got random sampling technical where two classes take a randomly from four classes there, VIII C as control class and VIII D as eksperiment class. The quetion validity tested with. Product moment corelation. The instrument reliability tested with KR-20 formula and got the reliabel criteria rt = 0,6924. The analysis technical used anakova test after this tested with analysis requirement induded disreminate normality test, variance homogenity, and connection linierity test.Descritively, the result of the study showed that propensity of learning natural science result at the eight grade student in SMP Negeri 1 Tepus Gunungkidul scool year 2013/2014 which through with quantum teaching learning and direct instruction included of high category. Inclination of critical thinking skill students with quantum teaching included very high category and while with direct instructionincluded high category. Comparatively there was significanly deference of science learning outcomer at the eight grade student in SMP Negeri 1 Tepus Gunungkidul in academic year 2013/2014 between used quantum teaching learning and direct instruction observed from critical thinking skill.